1947
DOI: 10.1002/jlac.19475580113
|View full text |Cite
|
Sign up to set email alerts
|

Zur Frage der Biogenese des Rutaecarpins und Evodamins. Die Synthese des Rutaecarpins unter zellmöglichen Bedingungen

Abstract: ist nach 3 Tagen beendet. Man dampft i. V. zur Trockne, reibt den Ruckstand zur Entfernung der BenzoesSure dreimal mit je 100 ccm abs. Ather durch, in dem das Oxyd schwer loslich ist, reibt weiter mit wenig abs. Alkohol an und lost den Ruckstand in heisem Alkohol, &us dem er beim Einengen mit dem konstanten Schmp. 112" auskrjstallisiert. Die Synthese des Rutaecarpins unter zellmoglichen Redingungenl)Voii Ckmens Schiipf uiid Horst Steuer f2)Aus den seit alters her in der ostasiatischen Medizin verwan dten Friic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1949
1949
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…We prepared 3 from Nb-formyltryptamine (12). A solution of the latter in dimethyl sulfoxide (DMSO) was treated with a solution of dimsyl sodium (2.25 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…We prepared 3 from Nb-formyltryptamine (12). A solution of the latter in dimethyl sulfoxide (DMSO) was treated with a solution of dimsyl sodium (2.25 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…They supported their biochemical studies by a chemical synthesis of rutaecarpine from 10 via 5 [67]. The carbon added to the N of tryptamine that would be the C2 of the quinazolinone ring, is generally afforded by formic acid, alkyl formate, triethyl orthformate, alkyloxycarbonyl halide, etc.…”
Section: Synthesismentioning
confidence: 99%
“…Schöpf and co-workers demonstrated that o-ABA 5 reacts with pyrrolines and piperidines to generate yellow-orange dihydroquinazolinium adducts. 14,15 In agreement with these observations, Vogel and Davis 16 report a yellow-colored dihydroquinazolinium compound when o-ABA 5 reacts with D 1 -pyrroline 6a and Larson et al 17 reveal that condensation of o-ABA 5 with D 1 -piperidine-6-carboxylic acid leads to an orange-colored dihydroquinazolinium derivative. Generation of the proposed adducts in the aforementioned studies presumably entails 1,2-addition of o-ABA 5 to the D 1 -pyrroline 6a or D 1 -piperidine 6b to generate an aminal 7 (Scheme 1).…”
Section: Introductionmentioning
confidence: 55%
“…Generation of the proposed adducts in the aforementioned studies presumably entails 1,2-addition of o-ABA 5 to the D 1 -pyrroline 6a or D 1 -piperidine 6b to generate an aminal 7 (Scheme 1). 14 dehydration, the dihydroquinazolinium species 9. Furthermore, reaction of reduced pyridine nucleotides with o-ABA 5 has been reported to produce an orange colored adduct under acidic conditions, with maximum color development occurring over a 30-60 min interval.…”
Section: Introductionmentioning
confidence: 99%